2007
DOI: 10.1002/sia.2595
|View full text |Cite
|
Sign up to set email alerts
|

XPS investigations of ink‐jet printed paper

Abstract: Different ink-jet printed paper materials were investigated using X-ray photoelectron spectroscopy (XPS) yielding the elemental composition of the near-surface region of the papers. We found significant differences with respect to the detected elements and their atomic concentrations in the different inks studied here. Two different groups of inks could be identified by means of a lower ratio of the O and C atomic concentrations and lower concentrations in specific trace elements like Mg, Na and Si. Highresolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The peaks at 284.5, 286.04, and 288.18 eV in the XPS spectrum of C 1s (Figure 5c) were attributed to the CC aromatic carbons, carbon atoms directly bonded to oxygen (COH and/or COC), and carbonyl groups, respectively (Malas et al, 2017; Singh et al, 2019; Zayed, Eisa, & Anis, 2022). The deconvolution of the O 1s spectrum revealed two components at around 532.04 and 532.9 eV that were ascribed to the CO groups and the oxygen of the phenol groups, respectively (Figure 5d) (Bourhis et al, 2011; Lützenkirchen‐Hecht et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…The peaks at 284.5, 286.04, and 288.18 eV in the XPS spectrum of C 1s (Figure 5c) were attributed to the CC aromatic carbons, carbon atoms directly bonded to oxygen (COH and/or COC), and carbonyl groups, respectively (Malas et al, 2017; Singh et al, 2019; Zayed, Eisa, & Anis, 2022). The deconvolution of the O 1s spectrum revealed two components at around 532.04 and 532.9 eV that were ascribed to the CO groups and the oxygen of the phenol groups, respectively (Figure 5d) (Bourhis et al, 2011; Lützenkirchen‐Hecht et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Modern XPS imaging instrumentation provide the lateral resolution, surface and elemental specificity, detection limit, and surface sensitivity needed to analyze inks and their crossings, and make confident conclusions about the features observed. XPS has been used to study ink‐jet printed paper and, although not explicitly a forensic study, discrimination between inks was reported 15 . It was not until 2010 when the potential of XPS analysis for forensics was publicly identified by Watts 16 .…”
Section: Introductionmentioning
confidence: 99%
“…XPS has been used to study ink-jet printed paper and, although not explicitly a forensic study, discrimination between inks was reported. 15 It was not until 2010 when the potential of XPS analysis for forensics was publicly identified by Watts. 16 Since then, the technique has been used in multiple forensic fingerprint studies, 17-20 but was not yet applied in forensic analysis of inks until recently as part of a round-robin study.…”
mentioning
confidence: 99%